2019
DOI: 10.1002/ejic.201900591
|View full text |Cite
|
Sign up to set email alerts
|

Steric Protection of Rhodium‐Nitridyl Radical Species

Abstract: In an attempt to synthesize a mononuclear rhodium nitridyl complex with a reduced tendency to undergo nitridyl radical N-N coupling, we synthesized a bulky analog of Milstein's bipyridine-based PNNH ligand, bearing a tert-butyl group at the 6′ position of the bipyridine moiety. A three-step synthetic route toward this new bulky tBu 3 PNNH ligand was developed, involving a selective nucleophilic substitution step, followed by a Stille coupling and a final hydrophosphination step to afford the desired 6-(tert-bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In specific regard to group 9–11 metals in tetragonal ligand fields, it is considered the case that d-orbital occupation with electron counts of n ≥ 4 is incompatible with metal–ligand multiple bonds, a concept that has been coined the “oxo wall”. ,, Yet, the oxo wall can be circumvented through lowering the coordination number and symmetry, employing sterically encumbering ligands, ,, and reducing the d-electron count through metal oxidation. ,, These strategies have been effective for a handful of Rh/Ir compounds such as the iridium­(V)­oxo Ir­(O)­(mes) 3 (mes = mesityl) synthesized by Wilkinson and nitride species such as (PNP)­Ir­(N) (PNP = N­(CHCHP t Bu 2 ) 2 ) reported by the groups of de Bruin and Schneider, among others. However, this can lead to nontrivial canonical forms, which complicates electronic structure interpretations and formal oxidation state assignments. , …”
Section: Introductionmentioning
confidence: 99%
“…In specific regard to group 9–11 metals in tetragonal ligand fields, it is considered the case that d-orbital occupation with electron counts of n ≥ 4 is incompatible with metal–ligand multiple bonds, a concept that has been coined the “oxo wall”. ,, Yet, the oxo wall can be circumvented through lowering the coordination number and symmetry, employing sterically encumbering ligands, ,, and reducing the d-electron count through metal oxidation. ,, These strategies have been effective for a handful of Rh/Ir compounds such as the iridium­(V)­oxo Ir­(O)­(mes) 3 (mes = mesityl) synthesized by Wilkinson and nitride species such as (PNP)­Ir­(N) (PNP = N­(CHCHP t Bu 2 ) 2 ) reported by the groups of de Bruin and Schneider, among others. However, this can lead to nontrivial canonical forms, which complicates electronic structure interpretations and formal oxidation state assignments. , …”
Section: Introductionmentioning
confidence: 99%
“…Although mononucleating lutidine-derived PNL (L = P, N, S or other) pincer ligands are mainly known for their MLC involving dearomatization–aromatization through Brønsted acid–base chemistry, their CPET chemical non-innocence reactivity is not unprecedented. 33 Pioneering work by Milstein and co-workers showed spontaneous H-atom loss from the methylene linker in [( R PNP)Co( i )-X] (X = CH 3 or H) complexes in solution at room temperature, resulting in paramagnetic species ( S = ) featuring a proposed ligand-centered radical. 34 Chirik and co-workers further investigated this and showed that the resulting paramagnetic complex is best described as a low spin Co( ii ) complex bearing a monoanionic ligand with a dearomatized pyridine core.…”
Section: Resultsmentioning
confidence: 99%